Covid-19 vaccine for transdermal delivery: formulation consideration and microneedle accession - Md.Minhaj-Ul-Alam (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.